Effet anti tumoral de l’extrait des noyaux d’abricots sur des souris soumises à un régime riche en nitrite de sodium - MAHI, Samira (My University, 2020)
Cancer is a disease caused by the cells transformation, which become abnormal and proliferate excessively. Cancer cells tend to invade nearby tissues and break away from the tumour. They then migrate through the blood and lymphatic vessels to make another tumour (metastasis). The aim of this work is to highlight the effect of apricot kernels against cancer. Cancer was induced by a daily oral administration of sodium nitrite (Na No2) for 5 months, in parallel, daily preventive and curative treatments were given by gavage of the extract of apricot kernels at a concentration of 100mg/kg in female mice (NMRI). The obtained results demonstrate that preventive and curative treatments were successful against tumours and even some haematological parameter with tissue improvement in the histological study.
Keywords: Cancer; Apricot kernels; Amygdalin; sodium nitrite; curation; prevention.